HUBUNGAN POLA ASUH MAKAN DENGAN STATUS GIZI ANAKUSIA PRA SEKOLAH (3-5 TAHUN) DI DUSUN KEJAGANDESA KEJAGAN KECAMATAN TROWULANKABUPATEN MOJOKERTO - Ma’rifah, Asirotul (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Preschool age children (3-5 years) were vulnerable nutrition groups, while they were undergoing a process of relatively rapid growth. If there was a lack of adequate child care, especially assuredness food then it became one of the factors that caused child malnutrition. The purpose of this research was to know the relationship between food parenting with nutritional status of preschool age children (3-5 years old) at Kejagan Sub Village Kejagan Village Trowulan Sub District Trowulan Mojokerto District. Research design was analytic correlation with cross sectional approach. Population was all mothers and preschool age children (3-5 years) as many as 31 people which were taken all as sample by using total sampling. Independent variable was food parenting and dependent variable was nutritional status of preschool age children (3-5 years). Data were taken by questionnaires to measure food parenting and trample scales, gauges and Family Card to measure the nutritional status. Then data were analysed by using cross tabulation. The results showed that majority (64,5%) of respondents did enough food parenting and nearly half (29,0%) did less food parenting. In addition, nearly half (29,0%) of respondents had children with nutritional status of overweight and wasted and a small portion (22,6%) had very wasted nutritional status. Results of cross-tabulations could be summed up that better food parenting had normal nutritional status and the lack of food parenting made more or less nutritional status. This was due to the better quality and quantity of parental care to the children made normal nutritional status of preschool children and vice versa.Keywords:foodparenting,nutritionalstatus,preschoolagechildren (3-5 years)